KOMUNIKASI PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KABUPATEN ACEH BESAR DI MASA PANDEMI COVID-19 - Putri Purnama Sari; Syahril Furqany (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2022)
This research focuses on marketing communications for Micro, Small and Medium Enterprises (MSMEs) in Aceh Besar during the Covid 19 Pandemic. It is very difficult to develop a business during a pandemic due to limited mobility. On the other hand, efforts must be made to sustain life. This research method uses a qualitative descriptive approach with a number of research informants as many as five MSMEs, namely Brownies Ratna, Crispy Udang Rebon Jihan, The Chip's By Zakiyah, Bungong Gallery and Tirta Kahveh Arabica Gayo Coffee. The results of the research of MSME actors in Aceh Besar continue to carry out prudok promotions by advertising through social media. Promoting various forms, for example giving tasters to potential customers and giving giveaways to regular customers. Provide the best service to consumers by getting used to providing correct and courteous information. In addition, Aceh Besar SMEs carry out promotions from one place to another to increase sales